Foreign Direct Investments (FDI) in Developing Countries – the Case of Southeast Europe - Muharem Klapić; Sead Omerhodžić; Amra Nuhanović (Ekonomski Vjesnik, 2013)
Foreign direct investment is one of the most important forms of international capital flow. Developed countries play a key role in capital flows, mainly as investors but also as beneficiaries. From the long-term perspective, the cyclic nature of investment flows in the global economy has been confirmed; however, over the past ten years, the participation of developed countries in FDI inflows has been declining, whereas at the same time the participation of developing countries has increased. In view of the above, this paper aims to highlight foreign direct investment importance and trends in the regional and sectoral structure in the developing countries, in particular the countries of Southeast Europe.